Clinical analysis of 20 cases of brain injury caused by diabetic ketoacidosis in children - Bin Zhou; Weiwei Chen; Shengxin Zhang; Yukun Huang; Chunzhi Chen; Yali Cai (BMC Pediatrics)
Abstract Objective To analyse clinical features and identify risk factors for brain injury in paediatric diabetic ketoacidosis (DKA), aiming to support early recognition and intervention. Methods A retrospective study was conducted on 20 children with DKA-related brain injury and 14 children with DKA without brain injury admitted to Xiamen Children’s Hospital between January 2022 and April 2024. Clinical data, laboratory findings, electroencephalography and magnetic resonance imaging (MRI) results were reviewed. Logistic regression analyses were used to identify influencing factors. Results Among the 20 children with DKA-related brain injury, 75% were girls, the median age was 7.3 years and 70% had severe DKA. Impaired consciousness was the primary symptom, presenting as lethargy (75%), dizziness (10%), somnolence (10%) and delirium (5%). Electroencephalography abnormalities were observed in 8 cases, and MRI changes were noted in 3 cases. Multivariate analysis identified a longer time to blood glucose stabilisation (odds ratio [OR] = 1.047, 95% confidence interval [CI]: 1.014–1.080, P = 0.005) and elevated insulin levels (OR = 1.217, 95% CI: 1.048–1.413, P = 0.010) as independent risk factors. Higher pH (OR = 0.002, P = 0.003), partial pressure of carbon dioxide (OR = 0.790, P = 0.007), serum bicarbonate (OR = 0.836, P = 0.010) and base excess (OR = 0.665, P = 0.015) were found to be protective. Conclusions Brain injury in paediatric DKA is associated with delayed metabolic correction. Early monitoring and timely regulation of acid–base balance and glucose levels may reduce the risk and improve outcomes.